Predictors of hyporesponsiveness to erythropoietin in prevalente hemodialysis patients and its association with mortality - Roldão,Marisa (2022)
ABSTRACT Introduction: Erythropoietin-stimulating agents hyporesponsiveness is common among hemodialysis patients. The aim was to analyze factors predictive of Erythropoietin-stimulating agent resistance and its association with mortality. Subjects and methods: Retrospective analysis of prevalent hemodialysis patients. Dose-response effect of Erythropoietin-stimulating agent therapy was evaluated using Erythropoietin-stimulating agent resistance index (ERI). Patients were classified in groups (ERI≤10 and ERI>10). All-cause mortality was assessed using standard survival methods. Results: Among 59 patients, 24 had ERI>10. Patients with ERI >10 had more central venous catheters, higher C-reactive protein levels, lower body mass index, serum iron, transferrin saturation, albumin and intact parathormone levels. Hyporesponsive patients had an increased risk of one-year mortality. Discussion and conclusion: Our study confirmed that malnutrition, inflammation, and iron deficiency are the main causes of Erythropoietin-stimulating agent hyporesponsiveness, and intact parathormone levels and central venous catheter use may also play a role. Erythropoietin-stimulating agent resistance appear to be associated with an increased mortality risk among prevalent hemodialysis patients.